Symbole i ich starzenie się w ujęciu Thomasa Carlyle ’a - Małecka, Anna (Stylistyka, 2021)
The paper discusses Thomas Carlyle’s symbolism - „clothes philosophy” - and the problem of ageing of symbols. First, the category of clothes as symbols is analysed, in the view of contemporary semiotics. Next, the spiritual meaning of clothes philosophy is outlined. In the Scottish philosopher’s opinion, clothes-symbols gradually wear out wi- thin the historie process, and can no longer “dress” the spirit. Baudrillard’s concept is quoted in this context. Carlylean inauthentic symbols become hollow shells or simulacra - signs with no reference to any reality which they were designed to point at, and - within certain limits - substitute. The need for new forms and „clothes”, which would appeal to contemporary generation, emerges, and the fundamental role here is to be played by hero- es. The tailor should be re-tailored, as the title of Carlyle’s masterpiece Sartor Resartus suggests.